Analisis karakter tokoh dalam novel ancika: dia yang bersamaku tahun 1995 karya Pidi Baiq berdasarkan pendekatan psikologi sastra - Dawis Syafitri; Rafika Muspita Sari (Universitas Asahan, 2023)
This study aims to deiscribei and eixplain: (1) thei characteirs in thei noveil Ancika: Dia yang Beirsamaku Tahun 1995 by Pidi Baiq; (2) Psychological conflicts of characteirs includei: Id, Eigo and Supeir Eigo characteirs in thei noveil Ancika: Dia yang Beirsamaku Tahun 1995 by Pidi Baiq. Thei theimei of this noveil is about thei romancei beitweiein Ancika and Dilan. This study useis a study of Liteirary Psychology. Thei meithod useid in this reiseiarch is deiscriptivei qualitativei that deiscribeis thei characteirs and psychological conflicts of thei characteirs including: Id, Eigo and Supeir Eigo of thei characteirs in thei noveil. Thei moral meissagei that can bei takein from thei noveil Ancika: Dia yang Beirsamaku Tahun 1995by Pidi Baiq is to beihavei in a frieindly and politei manneir towards anyonei in thei einvironmeint. noveil into teiaching mateirials or leiarning mateirials adapteid to thei applicablei curriculum.